Odpowiedź:
2)
A) (2x - 3) * (1 - 3x) = 2x - 6x² - 3 + 9x = - 6x² + 11x - 3
B) (3 - 2x) * (3x + 1) = 9x + 3 - 6x² - 2x = - 6x² + 7x +3
C) (3 - 2x) (1 - 3x) = 3 - 9x - 2x + 6x² = 6x² - 11x + 3
D) (3 + 2x) * (3x - 1) = 9x - 3 + 6x² - 2x = 6x² + 7x - 3
odp. C. 6x² - 11x + 3
4)
a) kwadrat
P = a²
P = (2a + 3)² = 4a² + 12a + 9
b) trapez
p = (podstawa + podstawa) * wysokosc / 2
podstawa gorna 2b
podstawa dolna 2a
wysokosc a - 3
(2a + 2b) * (a - 3) 2a² + 2ab - 6a - 6b 2 (a² + ab - 3a - 3b)
P = -------------------------- = ------------------------------- = ------------------------------- =
2 2 2
= a² + ab - 3a - 3b
Szczegółowe wyjaśnienie: